Alkali activation of recovered fuel-biofuel fly ash from fluidised-bed combustion Stabilisation/solidification of heavy metals - Yliniemi, Juho (Waste management (New York, N.Y.), 2015)
Copyright © 2015 Elsevier Ltd. All rights reserved.